2020
DOI: 10.33331/rechtsvinding.v9i1.408
|View full text |Cite
|
Sign up to set email alerts
|

Simplifikasi Regulasi Dengan Menggunakan Metode Pendekatan Omnibus Law

Abstract: <p><span lang="IN">Jumlah regulasi saat ini sudah terlalu banyak dan saling tidak harmonis, saling konflik, serta saling tumpang tindih antara regulasi yang satu dengan yang lain. Banyaknya regulasi sering juga disebut </span><em><span lang="EN-US">over regulated</span></em><span lang="IN">,</span><span lang="EN-US">banjir regulasi, atau obesitas regulasi</span><span lang="IN">.</span><span lang="IN"> </span><span lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…On the one hand, the decision to use the omnibus law method is understandable given Indonesia's current hyper-regulation problems, or regulatory obesity (Arief, & Ramadani, 2021). The omnibus law concept, which is capable of condensing dozens of regulations into a single law, can serve as a shortcut for synchronizing policies and streamlining regulations in Indonesia (Setiadi, 2020). On the other hand, it would be unjust to look at omnibus legislation solely from a positive perspective, ignoring any flaws or systemic implications that may arise.…”
Section: Concerning the Omnibus Law On Job Creation And Its Issuesmentioning
confidence: 99%
“…On the one hand, the decision to use the omnibus law method is understandable given Indonesia's current hyper-regulation problems, or regulatory obesity (Arief, & Ramadani, 2021). The omnibus law concept, which is capable of condensing dozens of regulations into a single law, can serve as a shortcut for synchronizing policies and streamlining regulations in Indonesia (Setiadi, 2020). On the other hand, it would be unjust to look at omnibus legislation solely from a positive perspective, ignoring any flaws or systemic implications that may arise.…”
Section: Concerning the Omnibus Law On Job Creation And Its Issuesmentioning
confidence: 99%
“…To contain the newly formulated provisions, Law No. 13 Year 2003 revokes and declares as null and void 6 ordinances and 9 laws simultaneously [16]. institutions that it is set forth in an integrated policy of Omnibus Law; f. There is guaranteed legal certainty and legal protection for policy-makers.…”
Section: Procedural Regulatory Reformmentioning
confidence: 99%
“…The current condition of Indonesian regulations, both from the quantity and quality perspectives, is relatively miserable [1]. Until now, there are no certain data of how many regulations are there in Indonesia since different numbers of regulations are presented by many data providers.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the concept of omnibus law is a method of making regulations that combine several rules with different regulatory substances into one regulation under one legal umbrella. The concept is also known as the omnibus bill which is often used in countries that adhere to the common law system such as the United States when forming a regulation (Setiadi, 2020).…”
Section: Introductionmentioning
confidence: 99%